Sustainable Land Use and Rural Development in Southeast Asia: Innovations and Policies for Mountainous Areas - Fröhlich, Holger L. (Springer Environmental Science and Engineering, 2013)
Sustainable Development; Landscape/Regional and Urban Planning; Agriculture